Religious statecraft: Narratives of persecution and diplomacy in the case of Byzantine, Aksum and Himyar - Rukuni, Rugare (HTS teologiese studies, 2021)
When reviewed against the background of Byzantine diplomatic correspondence, Aksum’s religious policy on the Arabian Peninsula is perceivable within a Constantinian religio-political matrix. Imperial letters from Byzantine to Aksum and Persia denote the Byzantine role of arbiter of early Christianity. Byzantine Rome’s role in Christianity when reviewed from diplomatic correspondence with allies and antagonists recounts narratives of orthodoxy and persecution. Parallel review of letters from Constantine and Constantius decodes the Christian kingdom of Aksum as a participant of 4th-century CE Constantinian dynamics. This review was enabled through document analysis.